Methods to assess patient preferences in old age pharmacotherapy: a systematic review - Eidam, Annette; Roth, Anja; Lacroix, Andre; Goisser, Sabine; Seidling, Hanna; Haefeli, Walter E.; Bauer, Jürgen M. (Patient preference and adherence, 2020)
Purpose: The aim of this systematic review was to identify methods used to assess medication preferences in older adults and evaluate their advantages and disadvantages with respect to their applicability to the context of multimorbidity and polypharmacy. Material and Methods: Three electronic databases (PubMed, Web of Science, PsycINFO) were searched. Eligible studies elicited individual treatment or outcome preferences in a context that involved long-term pharmacological treatment options. We included studies with a study population aged >= 65 years and/or with a mean or median age of >= 75 years. Qualitative studies, studies assessing preferences for only two different treatments, and studies targeting preferences for life-sustaining treatments were excluded. The identified preference measurement methods were evaluated based on four criteria (time budget, cognitive demand, variety of pharmacological aspects, and link with treatment strategies) judged to be relevant for the elicitation of patient preferences in polypharmacy. Results: Sixty articles met the eligibility criteria and were included in the narrative synthesis. Fifty-five different instruments to assess patient preferences, based on 24 different elicitation methods, were identified. The most commonly applied preference measurement techniques were "medication willingness" (description of a specific medication with inquiry of the participant's willingness to take it), discrete choice experiments, Likert scale-based questionnaires, and rank prioritization. The majority of the instruments were created for disease-specific or context-specific settings. Only three instruments (Outcome Prioritization Tool, a complex intervention, "MediMol" questionnaire) dealt with the broader issue of geriatric multimorbidity. Only seven of the identified tools showed somewhat favorable characteristics for a potential use of the respective method in the context of polypharmacy. Conclusion: Up to now, few instruments have been specifically designed for the assessment of medication preferences in older patients with multimorbidity. To facilitate valid preference elicitation in the context of geriatric polypharmacy, future research should focus on suitable characteristics of existing techniques to develop new measurement approaches for this increasingly relevant population.